Perceptions of Stunting: Negotiating Local and Medical Knowledge in Jeneponto, South Sulawesi - Nurlela, Andi; Muhammad, Sawedi; Arifin, Suryanto; Hariashari, Hariashari (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
The problem of stunting is still a complex social and health issue in Indonesia, including in Jeneponto Regency, South Sulawesi, which has the highest prevalence of stunting in the province. People in this region have a different understanding of the concept of stunting compared to the medical definition used by the government. This research aims to analyze how the people of Jeneponto build an understanding of stunting through negotiations between local knowledge and medical knowledge. The research uses a qualitative approach with phenomenological design. A total of 15 informants were selected purposively, consisting of parents of children under five, health workers, posyandu cadres, community leaders, and local government officials. Data were collected through in-depth interviews, participatory observations, and documentation studies, then analyzed inductively using manual coding techniques. The results of the study show that people do not view stunting as a health problem, but as a social opportunity to obtain nutritional assistance and economic support. The label "stunting" is interpreted as a survival strategy in a formal policy structure that provides access to resources. The conclusion of the study emphasizes that the stunting phenomenon in Jeneponto is the result of a social construction that reflects the adaptation of the community to state policies, so that efforts to handle it need to pay attention to the social context and local rationality of the community.